Reforming Mortgage Execution Norms to Enhance Justice for Debtors - Taufano, Martinus Al Ibrani Giga; Silalahi, Wilma (Jurnal Ilmu Hukum Kyadiren, 2025)
The execution of mortgage rights under Article 6 of Law No. 4 of 1996 grants creditors direct authority to sell collateral through public auctions without requiring a court order. However, this practice frequently results in procedural violations that harm debtors and undermine the principle of justice. This study aims to analyze the legal framework governing mortgage execution, identify common procedural violations in auction practices, and propose an ideal legal protection model for debtors. Employing a juridical-normative methodology, the study analyzes relevant laws and regulations alongside case documentation. The findings reveal a significant imbalance in the legal positions of creditors and debtors, primarily due to insufficient procedural oversight. The study concludes that reforming existing norms and enhancing supervisory mechanisms for execution auctions are essential to ensure legal certainty, protect debtor rights, and promote substantive justice within Indonesia’s collateral law system.